ANALYSIS OF STUDENTS’ PERSPECTIVE TOWARD IMPLEMENTATION OF CHARACTER EDUCATION - Afriana, (JEE (Journal of English Education), 2018)
The purpose of this study is to analyze students' perspectives toward how teachers in implement character education. Then, to analyze how teachers prepare in learning devices and inserting character education in the learning process in the form of RPS. Education is very decisive towards the formation of character, personality, character and character of students. Existing phenomena in the field such as crime, criminal acts, immoral actsand drug use, are considered as an impact of education that does not have character values in it. Moreover, there are many various frauds and crimes ranging from corruption, bullying, drugs in the school environment. The occurrence of various frauds and frauds indicates a lack of morals, character and national character. Realizing this, the Indonesian government through the Ministry of National Education launched a character education model to improve the character and character of the Indonesian people. This does not mean that previously there was no character education, but the government emphasized character education ina systematic manner. The first step in planting character education into the preparation and learning process. The teacher in this case is the key to the success of the application of character education because the teacher is directly dealing with students. Teachers in this case are required to prepare learning devices and then implement character education in the class. However, in the meantime the teacher is still not fully prepared to carry out this character education. Most teachers can insert the values of the nation's character into the Learning Implementation Plan but cannot be fully realized in the classroom. Meanwhile students are required to implement character education both at school and in the environment.